Existence, uniqueness and continuability of solutions of impulsive differential-difference equations. (1999) - Bainov, D. D.; Stamova, I. M.
Abstract : We consider an initial value problem for impulsive differential-difference equations, and obtain sufficient conditions for the existence, uniqueness, and continuability of solutions of such problem.